Revitalisasi Kawasan Air Terjun Bantimurung Gallang sebagai Upaya Peningkatan Peran Masyarakat Lokal dalam Pengelolaan Wisata - Wawan Andi Saputra; Jumriah Jumriah; Anisa Wulandari; Hardiyanti Dahlan; Nirma Ulfiyanah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The revitalization of village tourist areas is an important step to increase the attractiveness and sustainability of community-based tourist destinations. This study explains the application of an approach that involves participation in destination development in Pao village, Gowa Regency, especially in the Bantimurung Glang Waterfall area. The activities carried out include training in the field of services and improvement of the area, such as rearrangement of locations and installation of information boards, with the aim of strengthening community participation and improving facilities and services in the tourism sector. Preliminary data shows that the infrastructure and management system of the area still need to be improved, which can be seen from the low level of visitor satisfaction and the lack of supporting equipment. By using a participation-based service method, it is hoped that the management of the area can continue and empower the local community, as well as improve their knowledge and skills in managing tourist destinations. This approach not only focuses on the physical aspect, but also pays attention to the social and institutional aspects of the community, so that the community's ability to manage village tourism can be strengthened, supporting the sustainable and inclusive development of tourism villages.